Short-term rosuvastatin therapy prevents contrast-induced acute kidney injury in female patients with diabetes and chronic kidney disease: a subgroup analysis of the TRACK-D study - Li, Jing (J Thorac Dis, 2016)
BACKGROUND: Female patients are at higher risk of contrast-induced acute kidney injury (CIAKI) compared to males. In the multicenter, prospective, TRACK-D study, short-term rosuvastatin has proven effectively reduce CIAKI in patients with type 2 diabetes mellitus and stage 2-3 chronic kidney disease (CKD). This study aimed to explore the efficacy of rosuvastatin in the female TRACK-D population. METHODS: This study was a gender-based analysis of 2,998 patients (1,044 females) enrolled in the TRACK-D study and were randomized to short-term (2 days before and 3 days after procedure) rosuvastatin therapy or standard of care. The primary outcome was the incidence of CIAKI and the secondary outcome was a composite of death, dialysis/hemofiltration or worsening heart failure at 30 days. RESULTS: CIAKI incidence was comparable between male and female patients in the overall study population (2.5% vs. 3.4%, P=0.165) and in the rosuvastatin group (2.4% vs. 2.1%, P=0.72), while it was higher in females than in males in the control group (3.1% vs. 5.3%, P=0.04). Female gender was an independent risk factor of CIAKI [odds ratio (OR) =1.65; 95% confidence interval (CI), 1.03–2.63; P=0.036]. Rosuvastatin treatment vs. control lowered CIAKI rate in females [2.1% vs. 5.3%; relative risk (RR) =0.39; 95% CI, 0.19–0.77; number needed to treat (NNT) =31], particularly among those with CKD stage 2 (1.2% vs. 4.1%, P=0.011). Secondary outcome incidence was similar for females in the rosuvastatin and control groups (3.7% vs. 4.9%, P=0.37). CONCLUSIONS: Compared to males, untreated females with diabetes mellitus and CKD had a higher risk of CIAKI, which can be reduced by short-term rosuvastatin treatment.